Encapsulation of menthol into cyclodextrin metal-organic frameworks: Preparation, structure characterization and evaluation of complexing capacity. (15th February 2021) - Hu, Ziman; Li, Songnan; Wang, Shaokang; Zhang, Bin; Huang, Qiang
Highlights: Food-acceptable MOFs based on CDs were prepared to encapsulate menthol. Differences of structure and characteristics among various CD-MOFs were compared. β-CD-MOF showed apparently higher thermal stability than α-CD-MOF or γ-CD-MOF. The menthol content in β-CD-MOF was 3–4 times greater than for other reported materials. Abstract: Cyclodextrin (CD)-metal-organic frameworks (MOFs) are developed as a new type of food-acceptable multi-porous material, which shows a great potential for controlled volatile compound release. This study aimed to synthesize CD-MOFs from potassium nitrate, crystallized with α-cyclodextrin (α-CD), β-CD or γ-CD, and their complex capacities were further evaluated using menthol encapsulation. Compared with CD, all the CD-MOFs had highly ordered crystal structures and more regular shapes. β-CD-MOF showed better thermal stability, with an initial thermal degradation temperature of 253 °C, higher than the other two CD-MOFs. The CD-MOFs were used for menthol encapsulation and the resulting menthol concentration within the inclusion complexes (ICs) was determined. The menthol concentration in ICs followed the order: β-CD-MOF > β-CD > γ-CD-MOF > γ-CD > α-CD ≥ α-CD-MOF. The menthol content and encapsulation efficiency of β-CD-MOF were 21.76% (w/w) and 22.54% (w/w) respectively, significantly higher than those of other reported solid materials, such as amylose, CD and V-type starch.